NEONATAL DIABETES MELLITUS - IS TRISOMY 21 ASSOCIATED WITH REFRACTORY HYPERGLYCAEMIA? - Mirza, Adnan; Dhillon, Rubaid; Irfan, Omar; Ali, Amin; Salat, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Neonatal diabetes mellitus is a rare disorder characterized by refractory hyperglycaemia which is further divided into two types, transient (TNDM) and permanent neonatal diabetes (PNDM), which is associated with genetic aberrations at the human chromosome 6q24 accompanied with pancreatic structural abnormalities or b-cell dysfunction requiring insulin treatment. This case report analyzes a rare correlation between a case of permanent neonatal diabetes mellitus with Trisomy 21. Methods: An infant presented with intrauterine growth retardation and very low birth weight showing signs of persistent hyperglycaemia where genetic analysis suggested presence of permanent neonatal diabetes mellitus accompanied with Trisomy 21. Chest X-ray examination alongside an echocardiogram revealed significant pericardial tamponade. By the 6th week of life, pericardial effusion spontaneously resolved supported by normal follow-up echocardiograms without any treatment plan. The patient became euglycemic by 3rd week of life and discharged. Conclusion: Neonates with diabetes mellitus usually present with clinical features such as low-birth weight, ketoacidosis, consistent insulin-requiring hyperglycaemia and preterm. This case report shows a correlation between neonatal diabetes and genetic syndromes. Treatment plans can be improved by conducting genetic studies between these two variables and understanding the long-term outcomes.